A Variant of Application of Removable Lever for Turning Ellipsoid Bottoms of NPP Hull Equipment - P. D. Kravchenko; Y. P. Kosogova; M. A. Gashneva; A. F. Kovalev (Глобальная ядерная безопасность)
The paper present the calculation of the strength and rigidity of the removable gripper for moving and turning ellipsoid bottoms of hull equipment. The proposed design solution will reduce the labor and material consumption of technological equipment and eliminate the need for welded load-handling and installation elements.